Cognitive profiles in amyloid‐PET‐eligible patients: A retrospective study: Neuropsychology/Neuropsychological profiles of dementia: Valid biomarkers?. (7th December 2020) - Loreto, Flavia; Gunning, Stephen; Golemme, Mara; Watt, Hilary; Patel, Neva; Win, Zarni; Carswell, Christopher J.; Perry, Richard J.; Malhotra, Paresh A.
Abstract: Background: The early cognitive profile of Alzheimer's Disease (AD) is typically characterised by predominant impairment in episodic memory, reflecting medial temporal lobe dysfunction. However, little is known about the cognitive profile associated with AD pathology in those patients who meet Appropriate Use Criteria (AUC, Johnson et al., 2013) for Amyloid PET Imaging (API). In this group, AD pathology is frequently associated with an atypical clinical course or presentation. Here, we systematically evaluate the cognitive profiles of AUC‐meeting patients in a real‐world clinical setting, combining the information provided by the neuropsychological assessment with the results of Amyloid PET Imaging. Method: From a larger sample of 396 patients who underwent Amyloid PET at the Imperial Memory Centre between December 2013 and June 2019, we included those individuals who also had at least one formal neuropsychological assessment (minimum of 4 tests) within 18 months of API (n=124). Both these were solely conducted for clinical purposes, and API was requested after multidisciplinary team discussion. Cognitive measures in amyloid positive (Aβ+) and negative (Aβ‐) patients were compared using non‐parametric tests. Results: Neuropsychological assessment preceded Amyloid PET Imaging in most cases, for both amyloid‐positive (n=51, mean age 67.24±9.32 years, 58.8% female) and amyloid‐negative (n=73, mean age 67.9±9.64 years, 41.1% female) groups. Cognitive performance in the amyloid‐positive group was significantly worse in 6 of the 14 cognitive measures taken into account: visuo‐spatial functioning, executive functioning, working memory, verbal learning, verbal delayed recall, and confrontation naming (Figure 1). Verbal learning, verbal delayed recall and confrontation naming were the most frequently impaired measures in the amyloid‐positive group, with around 50% of patients performing below 2 standard deviations. Notably, self‐reported symptoms of depression were significantly higher in the amyloid‐negative (7.3±4.38) than in the amyloid‐positive group (4.68±3.7) (p=.002) ( Figure 2) . Conclusions: In a sample of patients attending a tertiary Behavioural Neurology clinic, neuropsychological evaluation revealed worse performance in positive API across a range of domains, particularly verbal memory and confrontation naming, with higher rates of symptoms of depression being reported more frequently in the amyloid negative group.